Peningkatan Pelayanan Lalu Lintas Penerbangan dengan Penentuan Perhitungan Expected Approach Time di Perum LPPNPI Cabang Palangka Raya - sasti, muhammad farhan sasri; Praptiningsih, Nunuk (Politeknik Penerbangan Indonesia Curug, 2023)
As a supporting airport for surrounding airports, Tjilik Riwut Airport must improve and maximize its air traffic services. One of the services given is the provision of clearance, one of which contains information on the estimated time to approach or expected approach time (EAT) where this information is the estimated time when the aircraft must leave the holding fix to start the approach to aircraft that are experiencing delays due to having a close arrival time, where the provision of this information has not been included in the clearance given to aircraft that will land at Tjilik Riwut Airport. This situation is considered to be disruptive to air traffic services and lack of efficiency in conducting air traffic services. Therefore, this research produces a calculation of the average time interval (ATI) using a quantitative descriptive method where the calculation of ATI affects the determination of the expected approach time. By determining the ATI, air traffic controllers can determine the EAT for aircraft that have an estimated time of arrival that is close to each other. In addition, EAT is very useful for determining a pilot approach and also helps in an emergency situation such as communication failure, etc.